Historical stages of the transformation of the judicial system and legal procedures in the Russian Empire: case of judicial reform of 1864 - Petrova, Irina A.; Romanov, Aleksey Yu.; Shestak, Victor A.; Trempolets, Liliia (Cuestiones Políticas, 2020)
The relevance of the study consists in the fact that the changes in the 1860-70s in the Empire determine the beginning of positive developments within the judicial system. Consequently, the objective of the article was to study the historical stages of the transformations in the judicial system and procedure in the Russian Empire in 1864. The main research method was deductive that allowed to study the nature and the key historical stages of the transformations in the judicial system and legal procedure in the Russian Empire in 1864. The solution to the problem posed was based on studying the legal foundations of the significance (place and function) of the judicial reform of 1864 within the general historical development of Russia. It is concluded that the key judicial principles include democratic foundations such as publicity in the oral process, frankness, and the right to a lawyer. Furthermore, it highlights that the authors of the Judicial Regulations of 1864 studied not only English and French law, but also examined the codes of procedure of Geneva and the Kingdom of Sardinia. Thus, the Russian jury trial became a new step in the development of European legal culture.